Model Evaluasi Pembelajaran pada Masa New Normal: Studi Kasus di SDN 04 Kalisari Kabupaten Grobogan - Nurfadhilah, Nada; Siregar, Ahmad Alkindi; Rabi'ah, Vira Muthia; Nudin, Burhan (el-Tarbawi, 2021)
Since Covid-19, schools implement the online learning system which gives extra tasks and responsibilities to all teachers. In online learning, the implementation of formative and summative evaluations has several problems, one of which is the limitations of media and learning evaluation tools. The purpose of this study is to explain and analyze (1) the implementation of summative and formative tests before the pandemic (2) the implementation of summative and formative tests during the new normal (3) The obstacles and supporting factors of the evaluation process at SDN 04 Kalisari. The research uses a qualitative approach. The data collection technique was carried out by indirect observation through the website, interviews via Zoom, and the study of documentation obtained in the form of data on school facilities and infrastructure. The technique of determining the informants used purposive sampling, namely the Principal and Teachers. The data analysis technique uses the Miles and Huberman model by means of data reduction, data presentation, and drawing conclusions. The conclusion of this study is that the implementation of formative and summative learning evaluations provides new achievements or new challenges for principals and teachers (1) The use of various learning methods to increasestudent interest (2) Smartphone and unstable network constraints (3) decreasedstudent scores. Keywords: Management; Evaluation; Learning; Pandemic.